2021
DOI: 10.1186/s13568-021-01287-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary recovery of hyaluronic acid produced in Streptococcus equi subsp. zooepidemicus using PEG–citrate aqueous two-phase systems

Abstract: Given its biocompatibility, rheological, and physiological properties, hyaluronic acid (HA) has become a biomaterial of increasing interest with multiple applications in medicine and cosmetics. In recent decades, microbial fermentations have become an important source for the industrial production of HA. However, due to its final applications, microbial HA must undergo critical and long purification processes to ensure clinical and cosmetic grade purity. Aqueous two-phase systems (ATPS) have proven to be an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…Santos et al ( 2018 ) reported extraction of 87.94% and 20.09-fold purified periplasmic l -ASNase from Escherichia coli with ATPS using PEG/Citrate system under optimized conditions. Primary (one-step) purification of other microbial products by PEG/Citrate aqueous two-phase system has also been reported by Flores-Gatica et al ( 2021 ) who recovered hyaluronic acid with 79.4% recovery and 74.5-fold purification factor. However, pre-purification of crude extract by ammonium sulfate precipitation before ATPS application significantly improved purification by 173.8-fold.…”
Section: Discussionsupporting
confidence: 54%
“…Santos et al ( 2018 ) reported extraction of 87.94% and 20.09-fold purified periplasmic l -ASNase from Escherichia coli with ATPS using PEG/Citrate system under optimized conditions. Primary (one-step) purification of other microbial products by PEG/Citrate aqueous two-phase system has also been reported by Flores-Gatica et al ( 2021 ) who recovered hyaluronic acid with 79.4% recovery and 74.5-fold purification factor. However, pre-purification of crude extract by ammonium sulfate precipitation before ATPS application significantly improved purification by 173.8-fold.…”
Section: Discussionsupporting
confidence: 54%
“…Diverse examples of successful polymer/salt systems for the recovery of biopolymers can be found in the literature. For example, Gatica et al [208] employed a PEG/citrate ATPS to extract microbial, high molecular weight hyaluronic acid. This polysaccharide was mostly extracted in the citrate-rich bottom phase (80%), and it could be recovered with a purity level of 75%.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…9 ATPS are formed when two water-soluble molecules (e.g., two polymers or a polymer and salt) are mixed above a certain critical concentration, when phase separation takes place. 9,10 This separation method has been used extensively for the separation of a wide type of biomolecules such as enzymes, 11 proteins, 12 peptides, 13 biopolymers, 14 antibodies, 15 and low-molecular-weight products, 16 among others molecules. Although several molecules from different sources have been recovered using ATPS, its use for snake venom fractionation has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%